THE EFFECT OF INSTITUTIONAL OWNERSHIP, MANAGERIAL OWNERSHIP, DEBT POLICY, AND DIVIDEND POLICY ON COMPANY VALUE - Avgoldson Prajnadi; Cheryl Regina; Audric Jordan; Jessy Safitri Sitorus (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This study aims to identify and analyze the Effect of Institutional Ownership, Managerial Ownership, Debt Policy, and Dividend Policy on Firm Value in banking sector companies that have been listed on the Indonesia Stock Exchange in 2016-2019. The research approach used is a quantitative approach. The sampling method is purposive sampling, a sample of 5 banking sector companies that have been listed on the Indonesia Stock Exchange in 2016-2019. The results show that institutional ownership, managerial ownership, debt to equity ratio, and dividend payout ratio have a simultaneous and significant effect on price to book value in banking sector companies that have been listed on the Indonesia Stock Exchange in 2016-2019. Institutional Ownership has a partial and significant effect on the price to book value of banking sector companies that have been listed on the Indonesia Stock Exchange in 2016-2019. Managerial ownership has a partial and insignificant effect on price to book value in banking sector companies that have been listed on the Indonesia Stock Exchange in 2016-2019. Debt to equity ratio has a partial and insignificant effect on price to book value in banking sector companies that have been listed on the Indonesia Stock Exchange in 2016-2019. Dividend payout ratio has no effect and is not partially significant on price to book value in banking sector companies that have been listed on the Indonesia Stock Exchange in 2016-2019